SISTEM PELAYANAN PENJUALAN ON LINE DI TOKO KOMPUTER MASCOM - Subakti Keristiawan; Dahlan Susilo; Sri Huning Anwariningsih (JURNAL GAUNG INFORMATIKA, 2014)
Mascom is a business entity engaged in the sale of computers. Mascom marketing system used today is in a conventional manner, it is necessary to use a marketing systemand internet web media. A matter that makes me create a website Mascom. This website is designed and equipped with e-commerce, to facilitate customer and manager of the website in the transaction.Preparation of final project using the waterfall method and object-based design. This website was built using xampp and wordpress.Website contains a informationabout the products are sold on Mascom computer. Testing of this system using the method of obtaining the result value McCall with 78.35%.This study resulted in an e-commerce website that can be accessed by potential buyers and prospective buyers so that Web visitors can find out information about theproducts offered detailed laptop and order the products.